A Review on Solar Calculator - Mool, Sneha; Sharma, Nitin (International Journal of Computer Sciences and Engineering, 2025)
The greater of the consumption energy, The use of diverse energy sources cannot be avoided. Therefore, assessment of the various sources of energy. Technologies continue to be developed. Photovoltaic technologies that convert solar energy directly into electrical energy using semiconductor devices is called solar cells. Solar energy apart easily obtained from natural, environmentally friendly too which does not produce carbon dioxide emmisions to Become a mainstay in the world of technology. The problem is to know how much you have saved using solar panel installation( to track your savings by using solar panels “solar calculator” is purposed. This will calculate your monthly savings, usage of SNDL, usage of solar panel).